Analisis Kesalahan Berbahasa Dalam Proses Pembelajaran Bahasa Indonesia Kelas IX SMP Negeri 2 Ciawi Pada Akun Youtube Neducitas Channel - Siska Aryani (LPPM Politeknik Pratama, 2023)
This study aims to analyze language errors in the Indonesian language learning process for class XI SMP Negeri 2 Ciawi on the Neducitas Channel Youtube Account. The method used in this research is descriptive with a qualitative approach. The subjects of this study were educators in the field of Indonesian language studies with the object under study, namely language errors made by educators because they did not use formal and/or standard language during the teaching and learning process. Based on the research data, it shows that there are errors that are categorized into 4 language errors, namely language errors in words and tenses, omissions, misordering, and informal ineffective sentences carried out by educators such as the use of the letter